Factors affecting young adults’ purchase intention of green food products in Malaysia / Tan Poh Leong and Audrey Malenee Mariadass - Leong, Tan Poh; Mariadass, Audrey Malenee (Faculty of Hotel & Tourism Management, 2019)
This study aims to analyse how factors such as willingness to pay, green advertisement and trust affect the intention to purchase green food. Furthermore, this study also intends to explore the role of green food product attributes as a mediator. Survey questionnaires were collected from 306 university students through purposive sampling technique. The data was analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) method. The findings indicated that green food product attributes have a significant mediation effect between the independent variables and purchase intention. The green advertisement was also found to have a complementary partial mediating effect. The interpretation of the results would shed light on the aspects that consumers value the most when considering purchasing green food products and how green food producers could better position and market their green food products to entice more people to try it.